2015
DOI: 10.1158/0008-5472.can-15-0377
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Heterogeneity in EGFR-Mutant NSCLC Results in Divergent Resistance Mechanisms in Response to EGFR Tyrosine Kinase Inhibition

Abstract: Non-small cell lung cancers (NSCLC) that have developed resistance to EGF receptor (EGFR) tyrosine kinase inhibitor (TKI), including gefitinib and erlotinib, are clinically linked to an epithelial-to-mesenchymal transition (EMT) phenotype. Here, we examined whether modulating EMT maintains the responsiveness of EGFR-mutated NSCLCs to EGFR TKI therapy. Using human NSCLC cell lines harboring mutated EGFR and a transgenic mouse model of lung cancer driven by mutant EGFR (EGFR-Del19-T790M), we demonstrate that EGF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 42 publications
7
116
0
Order By: Relevance
“…We have shown that HCC4006ER cells were insensitive to anti-microtubule agents that are often used as cytotoxic agents in non-small cell lung cancers [28]. These results may indicate that EMT is one of the most intractable cancer status, and treatment strategies that may prevent EMT (or downregulation of E-cadherin), such as upfront polytherapy as recently reported [30, 44, 45], may be needed in future development of treatment strategies.…”
Section: Discussionmentioning
confidence: 64%
“…We have shown that HCC4006ER cells were insensitive to anti-microtubule agents that are often used as cytotoxic agents in non-small cell lung cancers [28]. These results may indicate that EMT is one of the most intractable cancer status, and treatment strategies that may prevent EMT (or downregulation of E-cadherin), such as upfront polytherapy as recently reported [30, 44, 45], may be needed in future development of treatment strategies.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, among EGFR-mutant lung cancers with acquired resistance to their initial EGFR inhibitor, there is growing evidence that all resistant cells may not share the same, but exhibit different resistance mechanisms, likely reflecting both intratumoural and intertumoural heterogeneity, as well as dynamic changes in the relative populations of resistant clones over time143637. This problem adds to the potential benefit of blocking resistance with up-front combination approaches.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR mutation at L858R is a prerequisite for drug sensitivity 9. This specific mutation site appears in a restricted subset of NSCLC patients that includes those of East Asian ethnicity, women, and nonsmoking individuals 10. However, patients receiving tailored target therapy gradually develop secondary mutations in EGFR, which results in relapse 11.…”
Section: Introductionmentioning
confidence: 99%